Pharmacotherapy effects on smoking cessation vary with nicotine metabolism gene (CYP2A6). (11th November 2013) - Chen, Li‐Shiun; Bloom, A. Joseph; Baker, Timothy B.; Smith, Stevens S.; Piper, Megan E.; Martinez, Maribel; Saccone, Nancy; Hatsukami, Dorothy; Goate, Alison; Bierut, Laura
Abstract Background and aims Evidence suggests that both the nicotinic receptor α5 subunit (CHRNA5) and Cytochrome P450 2A6 (CYP2A6) genotypes influence smoking cessation success and response to pharmacotherapy. We examine the effect of CYP2A6 genotype on smoking cessation success and response to cessation pharmacotherapy, and combine these effects with those of CHRNA5 genotypes. Design Placebo‐controlled randomized smoking cessation trial. Setting Ambulatory care facility in Wisconsin, USA. Participants Smokers (n = 709) of European ancestry were randomized to placebo, bupropion, nicotine replacement therapy or combined bupropion and nicotine replacement therapy. Measurements Survival analysis was used to model time to relapse using nicotine metabolism derived from CYP2A6 genotype‐based estimates. Slow metabolism is defined as the lowest quartile of estimated metabolic function. Findings CYP2A6‐defined nicotine metabolic function moderated the effect of smoking cessation pharmacotherapy on smoking relapse over 90 days [hazard ratio (HR) = 2.81, 95% confidence interval (CI) = 1.32–5.99, P = 0.0075], with pharmacotherapy significantly slowing relapse in fast (HR = 0.39, 95% CI = 0.28–0.55, P = 1.97 × 10−8), but not slow metabolizers (HR = 1.09, 95% CI = 0.55–2.17, P = 0.80). Further, only the effect of nicotine replacement, and not bupropion, varies with CYP2A6‐defined metabolic function. The effect of nicotine replacement on continuous abstinence is moderated by the combined genetic risks from CYP2A6 and CHRNA5 (Wald = 7.44, d.f. = 1, P = 0.0064). Conclusions Nicotine replacement therapy is effective among individuals with fast, but not slow, CYP2A6‐defined nicotine metabolism. The effect of bupropion on relapse likelihood is unlikely to be affected by nicotine metabolism as estimated from CYP2A6 genotype. The variation in treatment responses among smokers with genes may guide future personalized smoking cessation interventions.